Crystallization and X-ray diffraction data analysis of human deoxyhaemoglobin A(0) fully stripped of any anions - Seixas, FAV; de Azevedo, W. F.; Colombo, M. F. (Munksgaard Int Publ Ltd, 1999)
In this work, initial crystallographic studies of human haemoglobin (Hb) crystallized in isoionic and oxygen-free PEG solution are presented. Under these conditions, functional measurements of the O-2-linked binding of water molecules and release of protons have evidenced that Hb assumes an unforeseen new allosteric conformation. The determination of the high-resolution structure of the crystal of human deoxy-Hb fully stripped of anions may provide a structural explanation for the role of anions in the allosteric properties of Hb and, particularly, for the influence of chloride on the Bohr effect, the mechanism by which Hb oxygen affinity is regulated by pH. X-ray diffraction data were collected to 1.87 Angstrom resolution using a synchrotron-radiation source. Crystals belong to the space group P2(1)2(1)2 and preliminary analysis revealed the presence of one tetramer in the asymmetric unit. The structure is currently being refined using maximum-likelihood protocols.